Study of Growth and Infectious Diseases in Children Under Five in The Work Area of Sikumana Health Center, Kupang City - Maria Yuniarsi Veranda; Lewi Jutomo; Daniela L. A. Boeky (Universitas Nusa Cendana, 2022)
Children under five are an age group that is vulnerable to nutritional problems and infectious diseases. Sikumana Health Center ranks second highest in Kupang City with 53 under-five children and 611 stunted children under five in 2018. In addition, Sikumana Health Center ranks first with 4503 cases of pneumonia and second for diarrhea with a total of 551 cases. This study aims to examine the growth and diseases that are often experienced by children under five in the working area of ​​the Sikumana Health Center, Kupang City. This type of research is descriptive quantitative. The population of this study was 3,832 children under five. Sampling using total sampling technique so that the sample size is the same as the population size. Data were analyzed based on the N/D ratio expressed in percent to determine the growth of children under five, and infectious diseases were analyzed based on the total number of medical visits for all children under five to the puskesmas which was reflected in the 10 most common diseases in children under five and expressed in percent. The results showed that the coverage of the growth of children under five was low (46.05%). Meanwhile, infectious diseases experienced by children under five include ARI (40.72%), Common Cold (18.61%), Gastroenteritis (5.61%), RFA (5.27%), TFA (4.30%), Diarrhea (4.30%), Rhinitis (3.58%), Bronchopneumonia (2 ,94%) and Bronchitis (2.45%). The coverage of the growth of children under five in the working area of ​​the Sikumana Health Center is in the low category, and the infectious diseases that are mostly experienced by children under five are more related to the respiratory system and digestive system.